2023
DOI: 10.1021/jacs.2c13439
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Mitochondria Import Aqueous FeII and, When Activated for Iron–Sulfur Cluster Assembly, Export or Release Low-Molecular-Mass Iron and Also Export Iron That Incorporates into Cytosolic Proteins

Rachel E. Shepherd,
Alexia C. Kreinbrink,
Cybele Lemuh Njimoh
et al.

Abstract: Iron–sulfur cluster (ISC) assembly occurs in both mitochondria and cytosol. Mitochondria are thought to export a low-molecular-mass (LMM) iron and/or sulfur species which is used as a substrate for cytosolic ISC assembly. This species, called X–S or (Fe–S)int, has not been directly detected. Here, an assay was developed in which mitochondria were isolated from 57Fe-enriched cells and incubated in various buffers. Thereafter, mitochondria were separated from the supernatant, and both fractions were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The results con rm the interplay between mitochondrial respiration and sterol biosynthesis, as has been previously evidenced [74]. Mitochondria harbours the heme and iron-sulfur (Fe-S) 2 cluster synthesis [75], which is essential for the activity of some sterol biosynthesis enzymes, and determinant in the oxidant radical formation [76]. In turn, the accumulation of toxic methyl sterols by, for instant, azoles treatment or loss of Erg25 or Erg27 activity, results in a rise in mitochondrial oxidants, a decrease in Fe-S production, and nally a loss of mitochondrial DNA [77,78].…”
Section: Mutations In Genes Involved In Sterol Productionsupporting
confidence: 81%
“…The results con rm the interplay between mitochondrial respiration and sterol biosynthesis, as has been previously evidenced [74]. Mitochondria harbours the heme and iron-sulfur (Fe-S) 2 cluster synthesis [75], which is essential for the activity of some sterol biosynthesis enzymes, and determinant in the oxidant radical formation [76]. In turn, the accumulation of toxic methyl sterols by, for instant, azoles treatment or loss of Erg25 or Erg27 activity, results in a rise in mitochondrial oxidants, a decrease in Fe-S production, and nally a loss of mitochondrial DNA [77,78].…”
Section: Mutations In Genes Involved In Sterol Productionsupporting
confidence: 81%
“…To measure siderophore transport, we treated S Tm with 57 Fe­(III)-loaded Ent or TC and monitored 57 Fe uptake by quantifying cell-associated 57 Fe by using inductively coupled plasma mass spectrometry (ICP-MS). As a stable, low abundance isotope (2.12% abundance vs 91.8% for 56 Fe), 57 Fe can effectively be used as a biological tracer; we and others have monitored the ratios of 57 Fe to other isotopes of Fe as an approach to track different Fe sources. We chose to measure uptake in S Tm as a case study because this gastrointestinal pathogen produces and utilizes Ent and employs both FepA and IroN to transport it across the OM, and we recently demonstrated that Ent-based SACs are highly active against S Tm . Additionally, S Tm only produces the catecholate siderophores Ent and salmochelin.…”
Section: Resultsmentioning
confidence: 99%